Analisis Perlakuan Akuntansi Pendapatan PSAK 23 pada Perusahaan Travel Umroh PT. Rangkayo Mulia Haramain - Muhammad Faris Al Amin; Rita Dwi Putri; Lili Wahyuni (Jurnal Ilmiah Raflesia Akuntansi, 2026)
The purpose of this study was to determine whether the measurement, recognition, disclosure, and accounting treatment methods for revenue at PT. Rangkayo Mulia Haramain Tour & Travel comply with PSAK No. 23. This study used a descriptive method with a quantitative approach. The data sources used in this research are primary through observation and interviews and the main source of the research is the company's financial reports. The results of the study indicate that revenue measurement at the company is carried out based on the transaction value agreed upon between the company and its customers. However, in recognizing revenue the company still uses the cash basis method, where revenue is recognized when cash is received by the company. This causes transactions that occur before cash is received not to be recorded as receivables, so the exact value of the company’s receivables cannot be determined. In addition, revenue disclosure in the financial statements has not clearly included accounting policies because the company still uses the cash basis method. Therefore, the accounting treatment of revenue applied by PT. Rangkayo Mulia Haramain Tour & Travel has not fully complied with PSAK No. 23.